Associations of folate intake with all-cause and cause-specific mortality among individuals with diabetes - Su, Hexin; Bo, Yacong; Zhang, Xiaoan; Zhang, Junxi; Gao, Zhan; Yu, Zengli (Frontiers in Nutrition, 2022)
Background & aims: The evidence regarding folate intake and mortality risk among patients with type 2 diabetes (T2D) remains unclear. This study aimed to investigate the association of folate intake with risk of mortality among individuals with T2D. Methods: A total of 9,196 participants with T2D from the Third National Health and Nutrition Examination Survey (NHANES III) and NHANES 1999–2014 were included. The data of survival were obtained by the cohort database linked with the national death index up to 31 December 2015. Cox proportional hazard model was used to evaluate the relationship between dietary folate with all-cause and cause-specific mortality. Results: Among patients with T2D, dietary folate-intake was negatively correlated with all-cause mortality, cardiovascular mortality and cancer mortality in men, and for women with all-cause mortality and cardiovascular mortality. The multivariate adjustment HR (95%CIs) for men of highest v.s lowest quartile was 0.77(0.66-0.90), 0.61(0.45-0.83) and 0.70(0.49-0.99) for all-cause, cardiovascular, and cancer mortality, respectively. Among women, the multivariate adjustment HR (95%CIs) of highest v.s lowest quartile was 0.77(0.64-0.92), 0.52(0.33-0.83) and 0.78(0.50-1.22) for all-cause, cardiovascular and cancer mortality, respectively. Conclusions: Higher dietary intake of folate were significantly associated with lower all-cause and cardiovascular mortality. This cohort study suggested that increasing the dietary folate intake may reduce mortality risk among U.S. adults with T2D.